Effect of the angle of seismic incidence on the response of a long-span curved bridge under spatially varying ground motions - Aziz Hosseinnezhad; Amin Gholizad (Numerical Methods in Civil Engineering)
The incidence angle of seismic waves affects the maximum response of bridges. Furthermore, long-span structures experience different seismic excitations at supports because of the spatial variability of ground motions. Moreover, for curved bridges, because of the irregular shape and the interaction between bending and torsion, the maximum response of the structure would be correlated to the input angle of the earthquake. In this study, the dynamic response of a long-span reinforced concrete curved bridge under asynchronous input motions for different inclinations of seismic incidence was investigated. For the numerical study, a curved plan bridge from the Caltrans bridges portfolio is selected and analyzed for various load and soil scenarios. The correlated arrays are generated by the method described in the paper and implemented to investigate the bridge. From the outcomes, the directionality effect of ground motions is evident that the responses change corresponding to the input angle of the seismic wave. For the case of multiple support excitations, the maximum response is different from the uniform load pattern. Finally, to find the most unfavorable input angles, an incremental dynamic analysis was performed. The results showed that the maximum response for each column occurs for different angles of earthquake incidence. The results showed that the responses of the structure increased under some angles of incidence. Additionally, responses from multiple-support were more varied in comparison with uniform excitations under different input angles, and in some cases larger than the responses caused by uniform excitations.